2009
DOI: 10.2105/ajph.2007.129528
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Antiretroviral Therapy and Increased Use of Contraceptives Among HIV-Positive Women During Expanding Access to Antiretroviral Therapy in Mbarara, Uganda

Abstract: Our findings support the need for increased attention to better integration of reproductive health and HIV and AIDS services for women who are HIV positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
69
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 21 publications
15
69
9
Order By: Relevance
“…Our study reveals high-risk behavior in HIVinfected patients undergoing care. This finding is consistent with a study conducted in Mbarara, Uganda, where 45% of 484 women had been sexually active in the previous three months, 85% reported using contraceptive methods but only about 60% reported using barrier contraceptive methods [8].…”
Section: Discussionsupporting
confidence: 91%
“…Our study reveals high-risk behavior in HIVinfected patients undergoing care. This finding is consistent with a study conducted in Mbarara, Uganda, where 45% of 484 women had been sexually active in the previous three months, 85% reported using contraceptive methods but only about 60% reported using barrier contraceptive methods [8].…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that women who have desire of children in future are less likely to use modern contraceptives. In fact, women living with HIV have strong desire of children due to the availability of drugs that prevent mother to child transmission of HIV [36].…”
Section: Discussionmentioning
confidence: 99%
“…2 It is diffi cult to assess in some women when a pregnancy is actually desired or not. The rate of induced abortion was remarkable in our study (31.0%) and was higher than the overall rate of 17.7% in childbearing women reported by Barbosa et al 3 (2009) in a study conducted in 13 municipalities in Brazil.…”
Section: Discussionmentioning
confidence: 99%